Examining Modernization on Higher Educational Institution: From Late Ottoman Period to the Modern Republic of Turkiye - Ahmad Siddiq (Proceeding International Conference on Religion, Science and Education, 2023)
Turkiye experienced its glory in the field of science during the peak reign of Fatih Sultan Mehmed & Kanuni Sultan Suleyman. Then fell with the defeat of the Ottoman Sultanate in the first world war and the rolling of a secular regime under the command of Atatürk. Looking at its educational history, Türkiye has indeed made efforts to reform and modernize to improve its higher education system. In the modern era, many scientists & intellectuals have emerged from Turkiye who have contributed to the development of modern science, such as Orhan Pamuk who won the Nobel Prize in literature, Aziz Sancar in chemistry, Ozlem Tureci and Ugur Sahin who discovered the COVID-19 vaccine, then Selcuk Bayraktar which has now succeeded in making unmanned military drones. This study aims to examine and elaborate in depth on the efforts that have been made by Turkiye in modernizing their higher education system from the late Ottoman period to the reign of the modern Turkish republic. This paper is qualitative research and uses a literature review. The author collects books and policies of the Turkish government as the main references, as well as related articles to obtain data. This study finds that in practice Turkiye has implemented several reform policies to modernize its higher education system. Several institutions had been established during the Tanzimat period to ensure modern teaching in higher education. In the current era, Turkish Universities also apply certain standards in ensuring progress in the development of science and technology in the country through quality assurance and internationalization of higher education.